Sustainability in agriculture by empowering farm women through ICT - BHARTI, MEETALI; BHARTI, DEEPSHIKHA (Journal of Soil and Water Conservation, 2020)
The lack of knowledge resources, lack of communication, and linkages with other agencies are causes of large gaps in adoption of new technologies in crop production, dairy management, and post-harvest management. To provide critical skills and technologies we must organize more and more women farmers clubs. Information Technology has the potential to increase the meaningful contribution of the women in the agriculture leading to a holistic development of agriculture sector. Women are considered effective communicator in disseminating agricultural technologies. Communication is a powerful tool and force for promotion food security, rural development through women engaged in agriculture. Effective communication can lead to the empowerment of women. This paper focused on some of the areas which would prove to be effective tool in communication such as; creation and development of web based information portal for the use of women, Developing database of women research in India and expert Information system, use of YouTube for dissemination of agricultural technology, which will be useful for farm women, Initiation of need based advisory service for farm women, publishing Journal/ Newsletter in regional language and distribution for effective dissemination for agricultural technology for the better use of farm women, starting Kissan Mobile Sandesh Seva in regional language, utilization of services of e-choupal by women, use of mobile communication and integration of SMS and mobile technology with community radio, role of mobile service as an effective ICT tools in transfer of agricultural technology and dissemination of agro-Met advisory bulletin with the application of ICTs regularly in order to apply corrective steps to strengthen the growth of agriculture.